A study of the tribological behaviour of TiO2 nano-additive water-based lubricants. (May 2017) - Wu, Hui; Zhao, Jingwei; Xia, Wenzhen; Cheng, Xiawei; He, Anshun; Yun, Jung Ho; Wang, Lianzhou; Huang, Han; Jiao, Sihai; Huang, Li; Zhang, Suoquan; Jiang, Zhengyi
Abstract: A ball-on-disk tribometer was employed to evaluate the lubrication performance and mechanisms of innovative TiO2 nano-additive water-based lubricants. Two experimental methods were applied to determine the optimal mass fraction of TiO2 . In the method I, lubricants were added onto the worn disk tracks at a predetermined time interval. In the method II, the disks were immersed in the lubricants continuously during the whole process of tribological tests. The results both indicate that the water-based lubricants can significantly reduce the coefficient of friction (COF). The 0.8 wt% TiO2 lubricant demonstrates excellent tribological properties including the lowest COF and the strongest wear resistance under all lubrication conditions. The lubrication mechanisms are attributed to the rolling and mending effects of the TiO2 nanoparticles. Highlights: The environment-friendly TiO2 nano-additive water-based lubricants with superb dispersity and stability were developed. Two innovative experimental methods were employed to evaluate the lubrication performance of the developed lubricants. The lubrication mechanisms of the TiO2 nano-additive water-based lubricants were investigated with clear evidence. The lubrication model was established based on the lubrication mechanisms.